lírica de Alice Ruiz S.: Imagens Poéticas, Mito e Sociedade: 2012. - Marques, Helena Maria Medina (2013)
This investigation about the work of Alice Ruiz S. is founded in criticism and phenomenology with theoretical approaches on imaginary, so that the recurrent symbols, myths and poetic images can be analysed. In addition, the time of production is also considered, as well as its relationship with the social context, the age, and the influences on the production of the poet, with theretical foundations in Durand, studies of relationship between author, text and social environment that are calles mythcriticism and mythanalysis. The critical-theoretical notions were based on Durand, Bachelard, Cassirer Brunel , Chevalier; Gheerbrandt , Merleau Ponty, Nunes, Mello,among others. The research includes the study of the lyrics of Alice Ruiz S. by using Durand's methodologies of mythanalysis, mythochritics as well as hermeneutics and the identification and myths, symbols and images.The corpus consists of the following works: Navalhanaliga (1980), Até 79, Paixão Xama Paixão (1983), Minimal, Pelos Pêlos (1984), Hai-Tropikai (1985), Rimagens (1985), Vice-versos (1988), Desorientais (1996), Haikai (1998), Alice Ruiz Série Paranaenses nº3. (1988), Poesia pra Tocar no Rádio (1999), Yuuka (2004), Salada de Frutas (2008), Conversa de Passarinhos (2008), Dois em Um (2010), Três Linhas (2009), Boa Companhia (2009), Jardim de Haijin (2010), Estação dos Bichos (2011). Through this study it was possible to identify and analyze the main symbols, myths and images, from the perspective of mythocritics, mythoanalysis and that allowed us to understand the influence of the socio-cultural context on the lyrics of Alice Ruiz S. Ruiz It was noted the frequent use of word play and rhymes, poems that reflect existential crisis related to the position of women and historical situation; orientalism; greek mythology and integration with I-lyric with nature in her poetry.